The Relationship between Economic Growth and Democracy: Alternative Representations of Technological Change - Almas Heshmati; Nam-Seok Kim (Institute of Labor Economics (IZA), 2017)
This study investigates the relationship between economic growth and democracy by estimating a nation's production function specified as static and dynamic models using panel data. In estimating the production function, it applies a single time trend, multiple time trends and the general index formulations to the translog production function to capture time effects representing technological changes of unknown forms. In addition to the unknown forms, implementing the technology shifters model enabled this study to find possible known channels between economic growth and democracy. Empirical results based on a panel data of 144 countries observed for 1980–2014 show that democracy had a robust positive impact on economic growth. Credit guarantee is one of the most significant positive links between economic growth and democracy. The marginal effects of credit guarantee and foreign direct investment inflows are stronger in democratic countries than they are in non-democratic ones. In order to check the robustness of these results, a dynamic model constructed with a flexible adjustment speed and a target level of GDP is also tested. The results of this dynamic model also support the positive impacts of democracy on economic growth.
Keywords: D24; O43; O47; P16; 330; economic growth; democracy; production function; single time trend; multiple time trends; general index; technology shifters; flexible adjustment speed; target level of GDP